PELATIHAN PACKAGING DAN SARANA PROMOSI MINYAK SEREH WANGI PRODUKSI KELOMPOK TANI “GEMA INDUSTRI” DESA OENENU KECAMATAN BIKOMI TENGAH KABUPATEN TTU - Satmalawati, Maria Magdalena Endah Mulat; Metboki, Bernadina; Fallo, Kristoforus (Jurnal Abdi Insani, 2025)
Citronella oil produced by the “Gema Industri” farmer group is the only processor of essential oils made from citronella plants (Cymbopogon nardus) in North Central Timor Regency (TTU). The location of this home industry is in Oenenu Village, Bikomi Tengah District and has been carried out since 2000 until now using very simple equipment. Citronella oil distillation activities are carried out twice a week including marketing activities. The demand for citronella oil, especially in TTU Regency, which is adjusted to the purchasing power of the community, is not limited to pure citronella oil, but other products such as mixing several ingredients for medicinal purposes according to local wisdom such as massage oil or for treating toddlers in the form of a mixture of coconut oil and citronella oil in a ratio of 5:1 and other herbal ingredients. The results from the sale of products created by the “Gema Mandiri” farmer group have allowed this farmer group to survive until now. Product marketing is still done manually and relies on acquaintances and regular customers and there have been no more modern marketing breakthroughs such as the use of promotional media and digital marketing. In addition, the packaging of citronella oil is still limited to one size variant (100 ml) and has not been well designed, namely made of transparent plastic that does not meet product safety requirements, on the other hand the labeling is still very simple and does not fully describe the benefits of the product. The purpose of PkM is to help the "Gema Industri" farmer group in increasing market share by improving safer packaging with various volume and presentation variations so that it can increase people's purchasing power. The method used in the PkM activity is carried out in 2 stages, namely lectures and training on the use of packaging and labeling and training in selling via the internet in this case promotion on social media. In this activity, the Community Service Team provided a transfer of IPTEKS on safe essential oil packaging such as the use of dark bottles that protect the product from direct sunlight. The community service team also introduced various forms and presentations of citronella oil with varying sizes starting from 10 ml in the form of a roll on so that it is more practical and affordable for the community, besides that there are other forms that are also practical in their presentation. Various packaging must also be supported by good promotional media, for that the devotion team designed a business leaflet that describes a brief profile of the "Gema Industri" Farmer Group, the steps for making citronella oil and also an introduction to the products produced. With this business leaflet, it is hoped that the Gema Industri Farmer Group will find it easier to promote its products and hopefully it will be better known by the public. Members of the farmer group are also trained on how to promote and sell citronella oil and other citronella oil products via the internet (website and social media) in addition to using the leaflets that are distributed and the participation of the farmer group in exhibitions. The devotion activity on the use of safe packaging for the production of citronella oil at the GEMA INDUSTRI Farmer Group in Oenenu Village has gone well and brought benefits to the group. Citronella oil products are currently packaged in a variety of attractive packaging variations, hopefully it can further increase public interest in using them.